Edge AI in Internet of Things - Lim, Xuan Zheng (Nanyang Technological University, 2021)
Traditionally, big data, such as social media, online shopping and business informatics are mainly created and stored at mega scale data centers. However, with the proliferation of mobile computing and IoT, the trend is in reversal.